Baseline neutrophil‐to‐lymphocyte ratio in patients with advanced melanoma treated with immune checkpoint inhibitors. (8th May 2018) - Machet, L.; Zaragoza, J.; Finon, A.; Garnier, M.; Maillard, H.; Caille, A.
Abstract : Linked Article: Fujisawa etal. Br J Dermatol 2018;179 :213–215 .